UPDATE ON SOUTHERN AND NATIONAL ACTIVITIES BY LABOR, AGRICULTURE AND LMC ALLIES (Tufts Archival Research Center, 2007)
Memorandum from Ogilvy, Adams & Rinehart detailing Labor Management Committee (LMC) strategies for opposition to 75 cent federal cigarette tax increase to finance Clinton Health Care Plan. Focuses on framing the issue as one of job loss, worker retraining, and regressive taxation. Relies on the support of allied interest groups, specifically labor, consumer, African-American, and agricultural groups. Provides plan to target Southern members of Congress, specifically those from Tennessee and the Florida panhandle.